Research progress of SREBP and its role in the pathogenesis of autoimmune rheumatic diseases - Xu, Xiaofen; Jin, Wumeng; Chang, Runyu; Ding, Xinghong (Frontiers in Immunology, 2024)
Autoimmune rheumatic diseases comprise a group of immune-related disorders characterized by non-organ-specific inflammation. These diseases include systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), ankylosing spondylitis (AS), gout, among others. Typically involving the hematologic system, these diseases may also affect multiple organs and systems. The pathogenesis of autoimmune rheumatic immune diseases is complex, with diverse etiologies, all associated with immune dysfunction. The current treatment options for this type of disease are relatively limited and come with certain side effects. Therefore, the urgent challenge remains to identify novel therapeutic targets for these diseases. Sterol regulatory element-binding proteins (SREBPs) are basic helix-loop-helix-leucine zipper transcription factors that regulate the expression of genes involved in lipid and cholesterol biosynthesis. The expression and transcriptional activity of SREBPs can be modulated by extracellular stimuli such as polyunsaturated fatty acids, amino acids, glucose, and energy pathways including AKT-mTORC and AMP-activated protein kinase (AMPK). Studies have shown that SREBPs play roles in regulating lipid metabolism, cytokine production, inflammation, and the proliferation of germinal center B (GCB) cells. These functions are significant in the pathogenesis of rheumatic and immune diseases (Abstract figure). Therefore, this paper reviews the potential mechanisms of SREBPs in the development of SLE, RA, and gout, based on an exploration of their functions.